Paragraph Writing as A Sensibility-Based Productive Skill - Suseno, Bambang (Ahmad Dahlan Journal of English Studies, 2015)
AbstractParagraph writing in the context of Academic Writing in a number of academies and universities in Indonesia is considered a skill whose mastery needs reasoning or logical thinking besides knowledge of grammatical rules, lexis, and also ability to translate from bahasa Indonesia into English effectively and efficiently.Logical thinking should be exercised ever since the student writers begin their initial up to the final phase of writing a paragraph. They may not necessarily pour down their ideas in sentences the way they like. This is because first of all they have to determine the main idea, also known as topic sentence, that needs formulating from the general subject or topic that is still too broad to be developed. To formulate the topic sentence, they have to exercise their logical thinking. Then, the main idea has to be supported by supporting sentences which are related to one another. The process of writing supporting sentences and their interrelationship should also be based on logical thinking. Finally, the paragraph is closed by means of a sentence which concludes the discussion of the whole paragraph.A paragraph that flows smoothly or, in other words, is readable is, without any doubt, the one that is effective and sensible.